Analysis of Financial Performance Economic Value Added Market Value Added to Company Value (Empirical Study of PT Toba Pulp Lestari Tbk 2019-2023) - Sirait, Enzelica; Sari, Pipit Buana (Universitas Negeri Medan, 2025)
This study aims to examine the influence of financial performance indicators (current ratio, debt-to-equityratio, inventory ratio, net profit margin) and economic value added, as well as market value added, on firm value asrepresented by the price-to-earnings ratio. This research employs a quantitative methodology. The data is obtainedfrom secondary sources, specifically the financial records of PT Toba Pulp Lestari TBK from 2019 to 2023. Theemployed method is multiple linear regression analysis with EViews 12. Conclusions can be derived from the studytitled Analysis of Financial Performance of Economic Value Added and Market Value Added in Relation to CompanyValue at Toba Pulp Lestari TBK from 2019 to 2023. Current Ratio (CR) positively and significantly influencescompany value, while Debt to Equity Ratio (DER) negatively and significantly impacts company value. InventoryTurnover (ITO) also has a negative and significant effect on company value. Net Profit Margin (NPM) positivelyaffects company value but is insignificant. Economic Value Added (EVA) and Market Value Added (MVA) bothpositively and significantly enhance company value.